The effect of using generative AI in education - Héjja Ferenc; Bartók Tamás; Kocsis Gergely (ЗУІ ім. Ференца Ракоці ІІ, 2025)
Abstract. Generative AI tools are the cutting edge solutions of complex AI related problems. While investigating state-of-the-art results related to the effect of GenAI in the literature, one can note that the trends most likely lead to the expectation of a positive effect on the middle and long run. In this work we provide a systematic overview of the literature related to the integration of Generative AI tools into education. Our goal is to collect the findings of the last two years to get a picture of how educators and university students use and feel about generative AI. In order to picture the actual state of awareness, integration and expectations related to generative AI we focus on describing the same three aspects about it, namely 1.Productivity, 2.Integration, 3.Challenges for two different groups: A. University students and B. Academic teachers.
Keywords: AI in education; generative AI tools